Angular distribution of cosmic rays from an individual source in a turbulent magnetic field - Harari, Diego Dario (2016)
We obtain the angular distribution of the cosmic rays reaching an observer from an individual source and after propagation through a turbulent magnetic field, for different ratios between the source distance and the diffusion length. We study both the high-energy quasirectilinear regime as well as the transition towards the diffusive regime at lower energies where the deflections become large. We consider the impact of energy losses, showing that they tend to enhance the anisotropy of the source at a given energy. We also discuss lensing effects, in particular, those that could result from the regular Galactic magnetic field component and show that the effect of the turbulent extragalactic magnetic fields can smooth out the divergent magnification peaks that will result for point like sources in the limit of no turbulent deflections.